Abrogation of the RNase activity of Erns in a low virulence classical swine fever virus enhances the humoral immune response and reduces virulence, transmissibility, and persistence in pigs. Issue 1 (1st January 2021) - Wang, Miaomiao; Bohórquez, José Alejandro; Hinojosa, Yoandry; Muñoz-González, Sara; Gerber, Markus; Coronado, Liani; Perera, Carmen Laura; Liniger, Matthias; Ruggli, Nicolas; Ganges, Llilianne
ABSTRACT: The prevalence of low virulence classical swine fever virus (CSFV) strains makes viral eradication difficult in endemic countries. However, the determinants for natural CSFV attenuation and persistence in the field remain unidentified. The aim of the present study was to assess the role of the RNase activity of CSFV E rns in pathogenesis, immune response, persistent infection, and viral transmission in pigs. To this end, a functional cDNA clone pPdR-H30 K-36U with an E rns lacking RNase activity was constructed based on the low virulence CSFV field isolate Pinar de Rio (PdR). Eighteen 5-day-old piglets were infected with vPdR-H30 K-36U. Nine piglets were introduced as contacts. The vPdR-H30 K-36U virus was attenuated in piglets compared to the parental vPdR-36U. Only RNA traces were detected in sera and body secretions and no virus was isolated from tonsils, showing that RNase inactivation may reduce CSFV persistence and transmissibility. The vPdR-H30 K-36U mutant strongly activated the interferon-α (IFN-α) production in plasmacytoid dendritic cells, while in vivo, the IFN-α response was variable, from moderate to undetectable depending on the animal. This suggests a role of the CSFV E rns RNase activity in the regulation of innate immune responses. Infection with vPdR-H30 K-36U resulted in higher antibody levels against the E2 and E rns glycoproteins and in enhanced neutralizing antibody responses when compared with vPdR-36U. These results pave the way toward a better understanding of viral attenuation mechanisms of CSFV in pigs. In addition, they provide novel insights relevant for the development of DIVA vaccines in combination with diagnostic assays for efficient CSF control.